Exploring the use of direct corrective feedback on writing an Undergraduate Thesis - Dani Samuel Budiawan; Hamamah Hamamah; Moh. Hasbullah Isnaini (Linguista: Jurnal Ilmiah Bahasa, Sastra, dan Pembelajarannya, 2022)
This study explored the use of direct corrective feedback in the Thesis Proposal writing course where the students are expected to develop their undergraduate thesis proposal at Universitas Brawijaya and how direct corrective feedback can help the students to deal with their academic writing. The data were obtained from six students who have taken the Thesis Proposal Writing course and one lecturer who taught the course using two instruments: an interview guide and observation checklists to triangulate and ensure the validity. The result showed that: (1) direct corrective feedback was employed by the teachers to help the students to deal with their writing because direct corrective feedback was the most suitable and comprehensive feedback  (2) the lecturer provided direct corrective feedback through Google Classroom and Google Documents for asynchronous meeting and Google Meet for synchronous meeting (3) Direct corrective feedback helped the students to deal with their writing since the students had high positive attitude and is preferred by the students  to revise their drafts. In teaching writing, the result implied that it will be very beneficial for the teacher to provide direct corrective feedback to the students as teaching strategies and the students to correct their drafts easily.